2009
DOI: 10.1038/nature08361
|View full text |Cite
|
Sign up to set email alerts
|

A luminal epithelial stem cell that is a cell of origin for prostate cancer

Abstract: In epithelial tissues, the lineage relationship between normal progenitor cells and cell type(s) of origin for cancer has been poorly understood. Here we show that a known regulator of prostate epithelial differentiation, the homeobox gene Nkx3.1, marks a stem cell population that functions during prostate regeneration. Genetic lineage-marking demonstrates that rare luminal cells which express Nkx3.1 in the absence of testicular androgens (castration-resistant Nkx3.1-expressing cells, CARNs) are bipotential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
707
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 651 publications
(747 citation statements)
references
References 49 publications
33
707
5
2
Order By: Relevance
“…More surprisingly, murine and human basal epithelial stem cells expressing high Trop2 and CD49f were also susceptible to malignant transformation [3,4]. Altogether, these exemplary studies demonstrated that both basal and luminal cell types contain potential cells of origin of prostate cancer [1,3].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…More surprisingly, murine and human basal epithelial stem cells expressing high Trop2 and CD49f were also susceptible to malignant transformation [3,4]. Altogether, these exemplary studies demonstrated that both basal and luminal cell types contain potential cells of origin of prostate cancer [1,3].…”
Section: Introductionmentioning
confidence: 72%
“…In addition to this, Wang et al showed luminal stem cells (CARNs) are also a cell of origin of prostate cancer in mouse prostate [1]. While the existence of CARNs and their susceptibility to malignancy in human prostate is yet to be discerned, it is plausible that prostate cancer may arise from multiple benign cell types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the predominant histological subtype of prostate cancer acinar-type adenocarcinoma has a luminal phenotype, any cell type capable of generating a luminal phenotype under normal conditions is a candidate for generating luminal tumours during transformation. Both basal and luminal cells have been previously demonstrated to differentiate into luminal cells and initiate murine prostate cancer [1,3,4]. The study from the Blanpain lab suggests that several progenitors are capable of differentiation into luminal cells.…”
Section: Progenitor Cells In Cancermentioning
confidence: 99%